Hidrogenação de ácido levulínico a gama-valerolactona empregando fosfetos de metais de transição suportados em sílica - Albuquerque, Flávia Pereira de (2016)
The following silica supported phosphides with loading of 30 wt% were prepared, characterized and evaluated for levulinic acid hydrogenation to γ- valerolactone: Ni2P, CoP, MoP, WP and Fe2P. The catalysts were prepared in two steps: phosphate synthesis by incipient wetness followed by calcination, and phosphide synthesis by in situ temperature programmed reduction. The samples were characterized by N2 physisorption at -196 ˚C, X-Ray diffraction, inductively coupled plasma optical emission spectrometry, CO chemisorption and temperature programed CO desorption. Temperature programed surface reaction experiments were also performed with 30 wt% Ni2P/SiO2. The catalytic evaluation were performed in a three phase trickle bed reactor, using H2 as hydrogen source and water as solvent, at 30 bar, 125 ˚C and weight hourly space velocity of 15 h -1 . In such conditions, theoretical calculations showed the absence of mass-transfer limitations. Among the evaluated phosphides, the best performance was obtained by 30 wt% Ni2P/SiO2 (conversion of 60%), based on the same weight of catalyst precursor loaded in the reactor, exhibiting a turnover frequency higher than the most effective catalyst for this reaction, 5% (m/m) Ru/C, to date. However, the supported phosphides suffered deactivation due to leaching of the active phase caused by water and increased by the presence of levulinic acid.